THE INFLUENCE OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE (Study in PT Pelayaran Samudera Selatan Jakarta) - Muhyi, Herwan Abdul (Universitas Pendidikan Indonesia, 2010)
Organizational culture and organizational commitment are the two factors that related to unoptimal employee performance The purpose of this research is to know, firstl; the implementation of organizational culture,organizational commitment, employee performance; and secondly, the influence of organizational culture and organizational commitment on the employee performancet. Variables of this research consist of organizational culture (X1), organizational commitment with subvariables; affective commitment (X2), continuance commitmen (X3), normative commitment (X4). and employee performance (Y).This research use explanatory method to explain causal relation among variables through hipotetical assessment. The population of the research is all employees worked in PT Pelayaran Samudera Selatan Jakarta. All of the employees became respondens of this research. The indicators of organizational culture are based on the Stephen Robbins Theory, organizational commitment indicators adoptedfrom Meyer and Allen Theory, and employee performance based on Bernardin and Russel theory. Generally, it is found that the perception to organizational culture, organizational commitment and employee performance of PT pelayaran Samudera Selatan can be categorized as good. From the path analyses, it is found that the organizational culture and organizational commitment has a strong positive impact either partially or simultancy on the employee performance.